Analisis Hasil Belajar Siswa dalam Penerapan Kurikulum Merdeka Belajar pada Pembelajaran IPAS Kelas IV di SDK Manumuti - Rofina Odilia Humoen; Damian Puling; Marsela Luruk Bere; Marianus Teti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Analysis Of Student Learning Outcomes In The Implementation Of The Merdeka Currikulum In IPAS Learning For Grade IV Students At SDK Manumuti” aims to examine: (1) The Learning Planning in grade IV SDK Manumuti using teaching tools provided by the ministry of education and culture; (2) The Implementation of IPAS learning in grade IV based on the merdeka curriculum at SDK Manumuti; and (3) The Evaluation of IPAS learning in grade IV using the merdeka curriculum. This study employed field research with a qualitative approach. Data were collected through observation, interviews, and dokumentation, using both primary and secondary data sources. Data analysis techniques included data reduction, data display, and conclusion drawing. The findings show that: (1) Lesson Planning in grade IV SDK Manumuti has been carried out using the teaching materials provided by the ministry of education and culture; (2) The Implementation of IPAS learning is conducted properly in accordance with the designed teaching modules, consisting of initial activities, core activities, and closing activities; and (3) The Evaluation of learning in Grade IV SDK Manumuti refers to assessments provited by the ministry of education and culture, using formative assessments in each lesson. However, not all assessment have been implemented, particulary the diagnostic assessment which assesessment which has not yet been applied in every leasson.